Pengaruh Kecukupan Modal, Tingkat Likuiditas dan Efisiensi Operasional Terhadap Profitabilitas pada BPR di Kabupaten Sidoarjo - Emalya Anggifta Firdyanti; Gede Putu Agus Jana Susila (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to examine the effect of capital adequacy (Capital Adequacy Ratio/CAR), liquidity level (Loan to Deposit Ratio/LDR), and operational efficiency (BOPO) on profitability (Return on Assets/ROA) of Rural Banks (BPR) in Sidoarjo Regency. The research uses a quantitative approach with multiple linear regression analysis, utilizing secondary data derived from quarterly financial reports published by the Financial Services Authority (OJK). The data is processed using SPSS software to analyze the relationships between the variables. The findings reveal that, on a partial basis, capital adequacy (CAR) and liquidity level (LDR) do not have a significant effect on profitability (ROA). However, operational efficiency (BOPO) is found to have a negative and significant impact on profitability, indicating that higher operational costs may reduce profitability. Furthermore, when assessed simultaneously, the three independent variables (capital adequacy, liquidity level, and operational efficiency) collectively have a significant influence on profitability. These results suggest that, while individual factors like CAR and LDR may not directly affect profitability, the overall operational efficiency plays a crucial role in determining the profitability of Rural Banks in the region.